Estimation of the Internal Dose Imparted by 18F-Fluorodeoxyglucose to Tissues by Using Fricke Dosimetry in a Phantom and Positron Emission Tomography - Tippayamontri, Thititip; Betancourt-Santander, Esteban; Guérin, Brigitte; Lecomte, Roger; Paquette, Benoit; Sanche, Léon (Frontiers in Nuclear Medicine, 2022)
Purpose: Assessment of the radiation dose delivered to a tumor and different organs is a major issue when using radiolabelled compounds for diagnostic imaging or endoradiotherapy. The present article reports on a study to correlate the mean 18F-fluorodeoxyglucose (18F-FDG) activity in different tissues measured in a mouse model by positron emission tomography (PET) imaging, with the dose assessed in vitro by Fricke dosimetry. Methods: The dose-response relationship of the Fricke dosimeter and PET data was determined at different times after adding 18F-FDG (0-80 MBq) to a Fricke solution (1 mM ferrous ammonium sulfate in 0.4 M sulfuric acid). The total dose was assessed at 24 h (~13 half-lives of 18F-FDG). The number of coincident events produced in 3 mL of Fricke solution or 3 mL of deionized water that contained 60 MBq of 18F-FDG was measured using the Triumph/LabPET8TM preclinical PET/CT scanner. The total activity concentration measured by PET was correlated with the calculated dose from the Fricke dosimeter, at any exposure activity of 18F-FDG. Results: The radiation dose measured with the Fricke dosimeter increased rapidly during the first 4 h after adding 18F-FDG and then gradually reached a plateau. Presence of non-radioactive-FDG did not alter the Fricke dosimetry. The characteristic responses of the dosimeter and PET imaging clearly exhibit linearity with injected activity of 18F-FDG. The dose (Gy) to time-integrated activity (MBq.h) relationship was measured, yielding a conversion factor of 0.064 ± 0.06 Gy/MBq.h in the present mouse model. This correlation provides an efficient alternative method to measure, three-dimensionally, the total and regional dose absorbed from 18F-radiotracers. Conclusions: The Fricke dosimeter can be used to calibrate a PET scanner, thus enabling the determination of dose from the measured radioactivity emitted by 18F-FDG in tissues. The method should be applicable to radiotracers with other positron-emitting radionuclides.